(untitled) (Journal of Comparative Social Work, 2014)
This article is based on a study of an educational and developmental programme, in which the task-centred coping approach (TCCA) was a central part. Twenty social worker practitioners from Norwegian municipal social services (MSS) participated in the programme, and practiced TCCA with 74 of their service users. The aim of the study was to develop knowledge about how service users evolve their housing competence by utilizing TCCA.The study was based on a way of participatory action research, in which the researcher was positioned as a partly participating researcher. The researcher tried to attain knowledge from the individualized activities of the service users and the practitioners, and use this knowledge as a contribution to developing their practice and the programme. User participation was one of the cornerstones of the study, and individualization meant matching the approaches of the practitioners to the experienced needs of the individual service user.